Statically improved fungal laccase-mediated biogenesis of silver nanoparticles with antimicrobial applications - Reem M. Alharbi, Shifaa O. Alshammari, Abeer A. Abd El Aty (Journal of Applied Pharmaceutical Science, 2023)
Green synthesis of silver nanoparticles (AgNPs) using microbial enzymes has gained great attention owing to its advantages, such as cost-effectiveness, biocompatibility, eco-friendliness, and simplicity, over conventional physical and chemical methods. In our study, the laccase enzyme of an unconventional source like the endophytic strain Alternaria arborescens MK629314 was optimized and applied for AgNP biogenesis. Alternaria arborescens laccase enzyme production was first improved using a three-factor, five-level central composite design of 20 trails; the low-cost medium of rice bran increased the laccase production to 6.5-fold. Second, the semipurified laccase enzyme was applied as a reducing and capping agent for the synthesis of AgNPs, and all the characteristics of the formed nanoparticles were studied. The applied techniques were transmission electron microscopy, UV-vis spectroscopy, Fourier transform infrared (FTIR), and dynamic light scattering (DLS). The results of all the analyses emphasized the formation of AgNPs. AgNPs biosynthesized from 25% and 50% semipurified enzyme fractions had size ranges of 6.51 ± 5.12 and 2.51 ± 3.45 nm and showed UV-characteristic peaks at wavelengths of 416 and 404 nm, respectively. DLS analysis presented good peaks with particle size means of 96.20 and 82.30 nm and zeta potentials of −58.3 and −98.5 mv. FTIR analysis showed the appearance of distinctive bands at 3,849.22, 3,440.39, 1,637.27, 1,432.85, 1,159.01, 1,031.73, 597.825, and 520.686 cm−1. The well diffusion method showed a good inhibition zone diameter of antibacterial efficiency against Escherichia coli and Staphylococcus aureus (15–17 mm) and antifungal activity against filamentous fungi Aspergillus niger and Fusarium solani (11–13 mm). The achieved results add to the growing relevance of A. arborescens as a potential applied endophytic fungus used for diverse biomedical applications.
Keywords: Laccase enzyme, Alternaria arborescens MK629314, central composite design (CCD), antimicrobial activity, silver nanoparticles